Evil-twin framework: a Wi-Fi intrusion testing framework for pentesters - Esser, André (2018)
In today’s world there is no scarcity of Wi-Fi hotspots. Although users are always recommended to join protected networks to ensure they are secure, this is by far not their only concern. The convenience of easily connecting to a Wi-Fi hotspot has left security holes wide open for attackers to abuse. This stresses the concern about the lack of security on the client side of Wi-Fi capable technologies. The Wi-Fi communications security has been a concern since it was first deployed. On one hand protocols like WPA2 have greatly increased the security of the communications between clients and access points, but how can one know if the access point is legitimate in the first place? Nowadays, with the help of open-source software and the great amount of free information it is easily possible for a malicious actor to create a Wi-Fi network with the purpose of attracting Wi-Fi users and tricking them into connecting to a illegitimate Wi-Fi access point. The risk of this vulnerability becomes clear when studying client side behaviour in Wi-Fi communications where these actively seek out to access points in order to connect to them automatically. In many situations they do this even if there is no way of verifying the legitimacy of the access point they are connecting to. Attacks on the Wi-Fi client side have been known for over a decade but there still aren’t any effective ways to properly protect users from falling victims to these. Based on the presented issues there is a clear need in both, securing the Wi-Fi client side communications as well as raising awareness of the Wi-Fi technologies everyday users about the risks they are constantly facing when using them. The main contribution from this project will be a Wi-Fi vulnerability analysis and exploitation framework. The framework will focus on client-side vulnerabilities but also on extensibility for any type of Wi-Fi attack. The tool is intended to be used by auditors (penetration testers - pentesters) when performing intrusion tests on Wi-Fi networks. It also serves as a proof-of-concept tool meant to teach and raise awareness about the risks involved when using Wi-Fi technologies.